Solid Pseudopapillary Neoplasm of the Pancreas in Children and Adults: A National Study of 369 Patients. Issue 4 (May 2018) - Leraas, Harold J.; Kim, Jina; Sun, Zhifei; Ezekian, Brian; Gulack, Brian C.; Reed, Christopher R.; Tracy, Elisabeth T.
Abstract : Background: Solid pseudopapillary neoplasm (SPN) of the pancreas is a rare tumor in children, with current evidence limited to single-center studies. We examined treatment and clinical outcomes for pediatric and adult SPN with a national data set. Methods: The 2004 to 2013 National Cancer Data Base was queried to identify all patients diagnosed with SPN. The cohort was stratified by age (pediatric and adult) defined as below 18 years and 18 years and above, respectively. Baseline characteristics and unadjusted outcomes were compared. Results: We identified 21 pediatric and 348 adult patients with SPN. Both groups displayed similar demographic composition. Patients were commonly female (90.5% [pediatric] vs. 85.9% [adult], P =0.56) and white (66.7% vs. 68.3%, P =0.74). Tumor location was similar between adults and children. Median tumor size was similar between children and adults (5.9 vs. 4.9 cm, P =0.41). Treatment strategies did not vary between groups. Partial pancreatectomy was the most common resection strategy (71.4% vs. 53.1%, P =0.80). Both groups experienced low mortality (0.0% vs. 0.7% at 5 y, P =0.31). Conclusions: This study provides the largest comparison of pediatric and adult SPN to date. Children with SPN have similar disease severity at presentation, receive similar treatments, and demonstrate equivalent postoperative outcomes compared with their adult counterparts.